Comprehensive Platelet Phenotypic Laboratory Testing and Bleeding History Scoring for Diagnosis of Suspected Hereditary Platelet Disorders: A Single-Institution Experience. Issue 1 (1st June 2017) - Perez Botero, Juliana; Warad, Deepti M.; He, Rong; Uhl, Cindy B.; Tian, Shulan; Otteson, Gregory E.; Barness, Ryan L.; Olson, Mary C.; Gossman, Susan C.; Charlesworth, Jon E.; Nichols, William L.; Pruthi, Rajiv K.; et al.
Abstract: Objectives: Patients with hereditary/congenital platelet disorders (HPDs) have a broad range of clinical manifestations and laboratory phenotypes. We assessed the performance characteristics of the International Society on Thrombosis and Haemostasis bleeding assessment tool (ISTH-BAT) and clinically validated platelet laboratory tests for diagnosis of HPDs. Methods: The records of 61 patients with suspected HPDs were reviewed and ISTH-BAT scores calculated. Results: Nineteen (31%) patients had thrombocytopenia, and 46 (75%) had positive ISTH-BAT scores. Thirteen and 17 patients had prolonged PFA-100 (Dade Behring, Miami, FL) adenosine diphosphate and epinephrine closure times, respectively. Twenty-two had abnormal platelet light transmission aggregation. Twenty-four had platelet transmission electron microscopy (PTEM) abnormalities (10 dense granule deficiency, 14 other ultrastructural abnormalities). Positive ISTH-BAT scores were associated with thrombocytopenia (P < .0001) and abnormal PTEM (P = .002). Twenty-three patients had normal results. Conclusions: ISTH-BAT identified patients with suspected HPDs but lacked a robust association with laboratory abnormalities. Despite comprehensive laboratory testing, some patients may have normal results.